2023
DOI: 10.3389/fpsyt.2022.1105496
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of ischemic stroke predicted by machine learning based on multi-modal MRI radiomics

Abstract: ObjectiveIncreased risk of stroke is highly associated with psychiatric disorders. We aimed to conduct the machine learning model based on multi-modal magnetic resonance imaging (MRI) radiomics predicting the prognosis of ischemic stroke.MethodsThis study retrospectively analyzed 148 patients with acute ischemic stroke due to anterior circulation artery occlusion. Based on the modified Rankin Scale (mRS) score, patients were divided into good (mRS ≤ 2) and poor (mRS > 2) outcome groups. Segmentation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Other studies of some prognostic predictions have found similar results [22][23][24][25][26][27][28][29][30][31][32][33][34][35]. In these studies, we can see that the performance of radiomics based on different types of images (MRI, CT and CTA) gives good results in predicting prognostic factors such as the mRS scale after AIS or the presence of disability after AIS.…”
Section: Prognostic Predictionsupporting
confidence: 69%
“…Other studies of some prognostic predictions have found similar results [22][23][24][25][26][27][28][29][30][31][32][33][34][35]. In these studies, we can see that the performance of radiomics based on different types of images (MRI, CT and CTA) gives good results in predicting prognostic factors such as the mRS scale after AIS or the presence of disability after AIS.…”
Section: Prognostic Predictionsupporting
confidence: 69%
“…A number of AI algorithms for outcome prediction of stroke patients based on MRI have used modified Rankin scales as a reference to predict stroke outcomes and were able to predict the likelihood of hemorrhagic transformation [ 42 , 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of thrombectomy can vary among patients, and it is crucial to identify factors that can predict the success or failure of the procedure. In recent years, there has been growing interest in studying the textural features of thrombi on native CT scans and their potential power to predict the outcome of thrombectomy [ 6 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%